2017
DOI: 10.22159/ajpcr.2017.v10i10.20064
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Phytochemical and High-Performance Thin Layer Chromatography Analysis of the Root Barks of Onosma Echioides

Abstract: Objective: Onosma echioides (OE) L., family Boraginaceae, is most recurrently used remedial herb, which is extensively dispersed all over India. It is used as purgative, bladder obstacle, liver chaos, kidney obstruction, sciatic pain, and gout. The study was meant to carry out the physicochemical, phytochemical, and high-performance thin layer chromatography (HPTLC) analysis on root bark of OE. Methods: The physicochemical parameters were carried out as per the World Health Organization guideline. The prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The chromatograms were scanned by a CAMAG TLC Scanner after spraying with respective spray reagents and dried at 100° in a hot air oven. The peak number with its height, area and R f values of fingerprint data were recorded by WIN CATS (1.3.4 version) software [9][10][11][12][13][14].…”
Section: Paper Chromatographymentioning
confidence: 99%
“…The chromatograms were scanned by a CAMAG TLC Scanner after spraying with respective spray reagents and dried at 100° in a hot air oven. The peak number with its height, area and R f values of fingerprint data were recorded by WIN CATS (1.3.4 version) software [9][10][11][12][13][14].…”
Section: Paper Chromatographymentioning
confidence: 99%
“…The results of accuracy and precision testing showed that the methods had met the accuracy and precision requirements (% UPK, 98-102%, and % KV, ≤2.0%) [10,12,13].…”
Section: Dyta Et Almentioning
confidence: 99%
“…Mainly the root extracts of O. echioides are applied as antiseptic for skin injuries, contusion and eruptions. The two main active components namely shikonin and alkannin (enantiomeric natural dyes) along with their oligomers is present in O. echioides root bark (SHOAIB et al, 2017). Shikonin is the major component and possess wound healing, anti-cancer activity and has shown apoptosis and cell cycle arrest in MDA-MB-231 and HCT-116 cancer cell lines (Barreto et al, Kumar et 475 al., 2007, Kumar et al, 2013.…”
Section: Introductionmentioning
confidence: 99%